Thermodynamic and acoustic behaviors of prefabricated composite wall panel. (December 2020) - Peng, Liu; Xiaoyong, Luo; Ying, Chen; Zhiwu, Yu; Dayou, Yu
Abstract: The thermodynamic and acoustic behaviors of prefabricated composite wall panel were investigated based on the heat transmission and acoustic principles. Moreover, the thermal conductivity formula of the prefabricated composite wall panel based on thermal conductivity equivalence method was proposed by deducing the solving process of thermodynamic parameters. Changes of sound reduction index and sound pressure level (SPL) of the prefabricated composite wall panel with sound frequency range were analyzed by experimental test and numerical simulation. The research results demonstrate that the thermal conductivity of wall panel can be calculated accurately by the thermal conductivity equivalence method. The calculation model of sound reduction index can be used to determine the sound reduction index in the middle and low frequency ranges. The designed wall panel has satisfying heat insulation and sound insulation with a heat transfer coefficient of 0.55 W/m 2 ·K and about the weighted standard acoustic pressure difference ( DnT, w ) of 42 dB.